Peningkatan Pengetahuan Ibu Hamil melalui Pendidikan Kesehatan - Dewi, Desak Putu Devita Kariyanti; Suwanti, Suwanti (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2021)
This is evidenced by maternal mortality and neonates mortality always still high. One way to reduce maternal mortality and neonates mortality is by early breastfeeding initiation. Many studies say that early initiation breastfeeding has great benefits to decrease neonates mortality. The intervention of early breastfeeding initiation at Antenatal class will be helping the mother receive knowledge and skill. This research is to know the influence of health education on antenatal classes with knowledge and skills of early breastfeeding initiation at Sedau Public Health Care. This research design uses Pre-experimental with approach one group pretest-posttest. The sampling technique is by purposive sampling amounted to 30 respondents. Intervention given in this research is Health education through lectures, videos, and demonstrations. Characteristic at Sedau Public Health Center which three categories are age, last education, and occupation. Most age in Sedau Public Health Center is age 20-35 years (79,8%). Last education highest is Elementary School and High School (57%). Most occupation is Housewife (66,7%). Before bringing intervention to mean is 64,67 and after bringing, intervention is 97,33. Increased knowledge of pregnant women is 32,7. Before giving intervention means of skill is 9,83 and after giving intervention is 94,33. The increase in the average pregnant women's skill is 84.5%. There’s an influence of health education on Antenatal class with knowledge and skill of early breastfeeding initiation p value=0,00 or p-value <α = 0,05. Can use demonstration media using phantom and video media in learners.